Desain Busana Kerja Formal Modular Berbasis Sustainable Fashion untuk Ekspresi Identitas Diri Wanita Karier - Listiani, Sri; Suryawati, Suryawati; Zahra, E. Lutfia (Serat Rupa: Journal of Design, 2026)
This study aims to design multifunctional clothing based on sustainable fashion, specifically intended for career women, with consideration of long-term functionality, flexibility, and the ability to express self-identity. The background of this research is rooted in the need for career women to have clothing that is not only practical and aesthetically pleasing but also environmentally friendly and capable of representing personal character. A quantitative method was used, involving five panelists consisting of designers, academics, and professional women as respondents. The researcher developed four sets of multifunctional black clothing designs: (1) a sleeveless blazer with long pants, (2) a detachable-sleeve blazer with waist accents, (3) a blazer with ruffles on the collar and cuffs, and (4) pants that can be converted into a skirt. Evaluations were conducted based on four main aspects: quality dimension (comfort, material strength, construction), design principles (form harmony, aesthetics, function), sustainability (eco-friendly materials, durability, maintenance), and self-identity (style alignment with user personality). The analysis results show that the second design received the highest overall score. The average score across all four designs was 89.6%, with sustainability and design principles emerging as the most prominent aspects. In conclusion, multifunctional clothing based on sustainable fashion proves to be a suitable solution for modern career women, fulfilling the needs for efficiency, style, and deep self-expression, while also supporting sustainable fashion practices